For a post-colonial queer theory: coloniality of gender and heteronormativity occupying the borders of translation - Belizário, Fernanda (2016)
Proceedings of the Fifth International Congress in Cultural Studies, University of Aveiro, Aveiro (Portugal), 7th, 8th and 9th of September 2016